Bending and uniaxial tensile strain effects on the critical current of REBCO coated conductor tapes. (June 2021) - He, Rui; Tan, Yunfei; Huang, Ziyi; Xie, Yiming; Wang, Guangda; Wang, Yifan; Wu, Qiong; Wei, Junwen
Highlights: The critical current degradation of three different YBCO coated conductors under bending and uniaxial tensile strain at 77 K and self-field were investigated. The bending tensile strain and uniaxial tensile strain dependence of critical current performance have a good agreement. All the tapes showed better bending tolerance under compressive strain than tensile strain. Abstract: Bending tolerance is one of the most fundamental mechanical properties of REBCO coated conductors for application to a superconducting coil. In this study, we investigated critical current degradation of REBCO coated conductors under bending and uniaxial tensile strain at 77 K and self-field with three different kinds of production from SuperPower Inc, Suzhou Advanced Materials Research Institute (SAMRI) and Shanghai Superconductor Technology (STT), respectively. All the tapes showed better bending tolerance under compressive strain than tensile strain, particularly for STT tapes, which showed no Ic degradation in compressive bending strain even with bending radius of 4.5 mm, but a 5% Ic degradation in tensile strain with bending radius of 6–6.5 mm. A uniaxial tensile strain test was also carried out to verify the dependence of Ic under tensile bending strain, the test results showed a good agreement between them. The tensile strain tolerance was 0.28–0.29% for STT tapes, 0.4–0.43% for SAMRI tapes, and 0.5–0.55% for SuperPower tapes.